2010
DOI: 10.1115/1.4002457
|View full text |Cite
|
Sign up to set email alerts
|

Development, Modeling, and Experimental Investigation of Low Frequency Workpiece Vibration-Assisted Micro-EDM of Tungsten Carbide

Abstract: This present study intends to investigate the feasibility of drilling deep microholes in difficult-to-cut tungsten carbide by means of low frequency workpiece vibration-assisted micro–electro-discharge machining (micro-EDM). A vibration device has been designed and developed in which the workpiece is subjected to vibration of up to a frequency of 1 kHz and an amplitude of 2.5 μm. An analytical approach is presented to explain the mechanism of workpiece vibration-assisted micro-EDM and how workpiece vibration i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 13 publications
0
23
0
Order By: Relevance
“…In the paper by Jia et al (1997), the mechanical signal was generated and transmitted to the tool-electrode, which was applied to remove material. On the other hand, Jahan et al (2010) attempted to drill micro-holes, where the tungsten carbide workpiece was being vibrated while the EDM process was carried out. Other studies employing similar configurations have been reported by Yeo and Tan (1999), Zhao et al (2002), Huang et al (2003), Sundaram et al (2008) and Yu et al (2009) for producing high aspect ratio of micro-holes on steel, stainless steel, titanium alloy and nitinol workpieces, respectively.…”
Section: Ultrasonic Assisted Edmmentioning
confidence: 99%
See 2 more Smart Citations
“…In the paper by Jia et al (1997), the mechanical signal was generated and transmitted to the tool-electrode, which was applied to remove material. On the other hand, Jahan et al (2010) attempted to drill micro-holes, where the tungsten carbide workpiece was being vibrated while the EDM process was carried out. Other studies employing similar configurations have been reported by Yeo and Tan (1999), Zhao et al (2002), Huang et al (2003), Sundaram et al (2008) and Yu et al (2009) for producing high aspect ratio of micro-holes on steel, stainless steel, titanium alloy and nitinol workpieces, respectively.…”
Section: Ultrasonic Assisted Edmmentioning
confidence: 99%
“…Although encouraging results have been shown, some issues still need to be solved. In the ultrasonic assisted machining processes, high frequency and amplitude vibration mechanisms are likely to deteriorate the surface quality and the dimensional accuracy of the machined parts (Jahan et al, 2010), and the machining energy only decreased 10%. In addition, with its high precision, laser processing has the potential to be incorporated in wider application areas.…”
Section: Hybrid Subtractive Manufacturing Processesmentioning
confidence: 99%
See 1 more Smart Citation
“…are employed [14]. They also tend to accelerate tool wear even though a higher material removal is achieved.…”
Section: Without Ultrasonic Vibrations With Ultrasonic Vibrationsmentioning
confidence: 99%
“…The application of low frequency vibration to the electrodes during the EDM process has been investigated in the past [83,84,14,85,13]. Ghoreishi and Atkin- the workpiece on the material removal rate, surface roughness and tool wear.…”
Section: Vibration-assisted Flushingmentioning
confidence: 99%